The image of travel journalism in television and periodicals of Kazakhstan - Ozenbayeva, N.T.; Ishanova, A.K. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
This article provides an investigation on the topic of travel journalism in domestic mass media. The article focuses on the image of travel journalism in periodicals and television of Kazakhstan. Study that underscores the increasing importance of travel journalism to public understanding of tourism, culture, and global interconnectedness. As traditional travel journalism grapples with competition from digital media, it will have to find ways to preserve its cultural and informative relevance. Based on case studies, this research analyzes the transformation of the genre within the Kazakhstan’s media space and audience perceptions, as well as the factors that formalize its growth. Through a detailed examination of the media study of leading models that exist in print and broadcast media, this study explores the impact of travel journalism as a tool for the promotion of tourism and cultural heritage of Kazakhstan. The main task of the research was to analyze well-known projects of domestic travel journalism and compare them to the foreign media.